2015
DOI: 10.1002/jbmr.2762
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of p38α MAPK Signaling in Osteoblast Lineage Cells Impairs Bone Anabolic Action of Parathyroid Hormone

Abstract: Intermittent parathyroid hormone administration (iPTH) increases bone mass and strength by stimulating osteoblast number and activity. PTH exerts its anabolic effects through cAMP/protein kinase A (PKA) signaling pathway in mature osteoblasts and osteocytes. Here, we show that inactivation of the p38a MAPK-encoding gene with the use of an osteocalcin-cre transgene prevents iPTH bone anabolic action. Indeed, iPTH fails to increase insulin-like growth factor 1 expression, osteoblast number and activity, and bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Although the authors reported that, in these animals, PTH-induced expression of Rankl is supressed, still the net effect of p38 deletion is reduced ossification, due to the inability of PTH to induce osteogenic genes. In addition, the authors establish the possibility that PTH activates p38 through cAMP/PKA signaling (Thouverey and Caverzasio, 2015b ). Mechanistically, it has been proposed that PTH increases both SMAD and p38 BMP signaling in MSCs (Yu et al, 2012 ).…”
Section: Signaling Triggers P38 In Osteoblast Functionmentioning
confidence: 95%
“…Although the authors reported that, in these animals, PTH-induced expression of Rankl is supressed, still the net effect of p38 deletion is reduced ossification, due to the inability of PTH to induce osteogenic genes. In addition, the authors establish the possibility that PTH activates p38 through cAMP/PKA signaling (Thouverey and Caverzasio, 2015b ). Mechanistically, it has been proposed that PTH increases both SMAD and p38 BMP signaling in MSCs (Yu et al, 2012 ).…”
Section: Signaling Triggers P38 In Osteoblast Functionmentioning
confidence: 95%
“…Primary osteoblast were isolated from long bones of Pdgfra f/f ; Pdgfrb f/f mice as previously described. (24) Briefly, bone chips were prepared from cleaned long bones and digested in 1 mg/mL collagenase II (Sigma) for 90 minutes at 37 C. Bone pieces were washed several times and incubated in α-MEM (Amimed, Bioconcept, Salem, NH, USA) containing 10% FBS (Gibco) for 9 days to allow cell migration from bone fragments. At that point, cells and bone chips were trypsinized (with trypsin/EDTA from Sigma) and passaged at a split ratio of 1:3.…”
Section: Osteoblast Culturesmentioning
confidence: 99%
“…Osteoblasts were isolated from long bones of Ocy-PPARg 2/2 and Ocy-PPARg +/+ mice as previously described (22). Osteoblasts were seeded at 60,000 cells per well in 12-well plates.…”
Section: Primary Osteoblast Culturesmentioning
confidence: 99%
“…To investigate the proof of concept that deletion of PPARg in bone cells is able to prevent hepatic steatosis, improve FA metabolism by adipocytes, and augment pancreatic islet insulin secretion, we applied CM or performed real cocultures of mature osteoblasts with hepatocytes, adipocytes, and pancreatic b-cells. For this purpose, primary OB-OCY of Ocy-PPARg 2/2 and Ocy-PPARg +/+ were extracted from long bones as previously described (22). After 21 days of culture, CM was collected and added to primary hepatocytes from WT mice incubated with a mix of oleate and palmitate for 48 h to induce steatosis (Fig.…”
Section: Osteokines Secreted By Ocy-pparg 2/2 Mice Control Adipose Lmentioning
confidence: 99%